Sleep Quality and the Stress-Buffering Role of Religious Involvement: A Mediated Moderation Analysis - Ellison, Christopher G. (Journal for the scientific study of religion, 2019)
Although several studies have documented an inverse association between stressful events and sleep quality, much less is known about the factors that might moderate or buffer against the adverse effects of psychosocial stress on sleep. Building on previous research, we employ national cross-sectional survey data from the 2017 Baylor Religion Survey (n= 1,410) to test whether the association between recent stressful events and sleep quality varies according to several dimensions of religious involvement. We also formally assess whether any attenuation of the association between stressful events and sleep quality is at least partially mediated or explained by lower levels of depressive symptoms (mediated moderation). Our moderation analyses indicate that the inverse association between stressful events and sleep quality is in fact attenuated by religious cognitions (secure attachment to God and assurance of salvation), but not religious attendance or private religiousness. We also observe direct evidence of mediated moderation through depressive symptoms for both religious cognitions. Taken together, our results demonstrate that religious cognitions may buffer against stress-related sleep disturbance by helping people avoid symptoms of depression.